2012
DOI: 10.1007/s00381-012-1864-z
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric crushing head injury: biomechanics and clinical features of an uncommon type of craniocerebral trauma

Abstract: The observed skull, brain, and cranial nerve lesions corresponded to a mechanism of bilateral compression of the children's heads mainly occasioned by a static load, although an associated component of dynamic forces was also involved. The skull and its covering and the cranial nerves were the most severely affected structures while the brain seemed to be relatively well preserved. Most crush injuries appear to be preventable by the appropriate supervision of the children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…TBI can also result from static or near static loads that essentially crush the brain and skull, resulting in direct compression of the brain or contusion injury via bone fragments (Denny-Brown and Russell, 1940; López-Guerrero et al, 2012; Mattei et al, 2012). In these crushing or nutcracker injuries, the head is generally not subjected to the rapid linear or rotational movements that occur during impact injuries.…”
Section: Biomechanical Principles Of Tbimentioning
confidence: 99%
“…TBI can also result from static or near static loads that essentially crush the brain and skull, resulting in direct compression of the brain or contusion injury via bone fragments (Denny-Brown and Russell, 1940; López-Guerrero et al, 2012; Mattei et al, 2012). In these crushing or nutcracker injuries, the head is generally not subjected to the rapid linear or rotational movements that occur during impact injuries.…”
Section: Biomechanical Principles Of Tbimentioning
confidence: 99%
“…Crushing Head injury, as the name implies, occurs when the brain and skull are crushed-usually between two hard objects [1][2][3] . The more forceful the crushing is, the more severe damage will be, but damage also depends on factors such as the location of the injury and Hardness of the Impacting Object [Bludgeon].…”
Section: Introductionmentioning
confidence: 99%
“…Although the results of the Yousefzadeh Chabok et al’s investigation are particularly interesting in terms of the lucid format used to present the data, it would be more interesting if the authors could have reported other injuries that are commonly associated with head traumas such as brains contusions, intracranial hematomas, fractures of the skull vault and of the skull base, external signs of trauma as scalp wounds or soft tissue hematomas, bleeding from the nose, ears, or throat, and uni- or bilateral involvement of one or more cranial nerves (2). Moreover, the authors might also have reported the influence of temporal factors in the incidence of head injuries in their study population, since the results of epidemiologic investigations vary depending on the demographics of the population studied.…”
mentioning
confidence: 99%
“…Moreover, the authors might also have reported the influence of temporal factors in the incidence of head injuries in their study population, since the results of epidemiologic investigations vary depending on the demographics of the population studied. Factors such as geographic region, socioeconomic status, cultural differences, and temporal factors including time of the year and era, which could have impact on both the type and frequency of injuries in the population (2, 3). This sort of data is normally accessible from medical charts.…”
mentioning
confidence: 99%
See 1 more Smart Citation